Autophagy is influenced by vitamin D3 level in people with HIV-1 - Rita Casetti; Fabiola Ciccosanti; Harpreet Kaur Lamsira; Carmela Pinnetti; Valentina Mazzotta; Serena Ciolfi; Alessandra Sacchi; Alessandra Amendola; Giuseppe Ippolito; Mauro Piacentini; Roberta Nardacci (Biology Direct)
Abstract Background Autophagy is the primary catabolic process responsible for degrading intracellular components and potentially harmful cytosolic entities by delivering them to lysosomes. Notably, this mechanism is crucial for controlling intracellular pathogens, with significant implications for both innate and adaptive immunity. In the context of HIV-1 infection, emerging evidence suggests that autophagy contributes to immune responses against the virus. Various compounds can modulate autophagy, among which vitamin D₃ is particularly effective due to its ability to prevent inflammation and slow HIV-1 disease progression. Indeed, vitamin D₃ contributes to regulating both innate and adaptive immunity, thereby modulating antiviral and antibacterial inflammatory responses. Importantly, vitamin D₃ deficiency is highly prevalent among people with HIV (PWH) and has been associated with an increased risk of severe disease progression. Results In this study, we investigated the relationship between serum vitamin D₃ levels and the expression of autophagy markers in peripheral blood mononuclear cells from different categories of PWH: PWH under antiretroviral therapy (ART) with either normal vitamin D₃ levels or hypovitaminosis, and treatment-naïve PWH with either normal vitamin D₃ levels or hypovitaminosis. Our results show that low vitamin D₃ blood levels is associated with lower expression of the main factors involved in the autophagy mechanism, particularly in treatment-naïve PWH. Conclusions Our findings suggest that normal blood level of vitamin D₃ may play a crucial role in promoting autophagy in PWH. The observed differences in autophagy-related protein expression between ART-treated and untreated individuals underscore the intricate relationship between vitamin D₃ levels, ART exposure, and autophagic regulation. This is a preliminary exploration of the effects of vitamin D₃ on autophagy in PWH. Further studies are needed to deepen and explore the interplay between vitamin D₃ and autophagy in greater depth. A better understanding of these mechanisms could help to develop novel therapeutic strategies aimed at mitigating immune depletion and chronic inflammation, ultimately improving clinical outcomes for individuals living with HIV.